Perancangan Online Personality Test untuk Mengukur Kepribadian Calon Mahasiswa Universitas Pembangunan Jaya - Muthiah, Syifa Alya; Yulianto, Aries (Jurnal Psikologi : Media Ilmiah Psikologi, 2021)
AbstractMistakes in choosing a course of study can make students decide to change study programs or even move universities. This mistake happened at Universitas Pembangunan Jaya (UPJ) where there were 13 students moved study programs from 2017-2019, where 85% of the reason was because the study program that had been taken was not his own desire and was not in accordance with students. The choice of study program is influenced by many factors, one of which is personality. Based on the big five personality theory, there are 5 personality dimensions, namely Openness to experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism (OCEAN). This study aims to compile an online test to measure the personality of prospective UPJ students whose results can provide recommendations for suitable UPJ study programs. Researchers also conducted a preliminary psychometric test study of this personality test. This online administration makes use of a Google Form linked to a Google Sheet to create a scoring system and interpretation of results. This personality test consists of 50 Likert scale formatted statements, where each dimension is measured by 5 statements, from "Disagree" (1) to "Agree" (5). The test-retest reliability coefficient with a duration of 1 week for the five dimensions ranged from 0.585 to 0.952, while the Alpha coefficient of each dimension ranged from 0.449 to 0.757. The results of the construct validity test using the group difference technique showed that there was no difference in GPA between students whose personality test results were in accordance with the study program's recommendations and students whose personality test results did not match the study program recommendations. The developments of this online personality test will be continued in order to obtain satisfactory results. Keywords : online test, personality, big five personality, prospective college students, validity, reliability AbstrakKesalahan dalam memilih program studi dapat membuat mahasiswa memutuskan untuk pindah pindah program studi atau bahkan pindah perguruan tinggi. Hal ini juga terjadi di Universitas Pembangunan Jaya (UPJ) dimana tercatat ada 13 mahasiswa yang pindah program studi dari tahun 2017-2019, dimana 85% alasannya karena program studi yang telah diambil bukan keinginan dari diri sendiri dan tidak sesuai dengan dirinya. Pemilihan program studi dipengaruhi banyak faktor, salah satunya kepribadian. Berdasarkan big five personality theory, ada 5 dimensi kepribadian, yaitu Openness to experience, Conscientiousness, Extraversion, Agreeableness, dan Neuroticism (OCEAN). Penelitian ini bertujuan untuk menyusun tes online untuk mengukur kepribadian calon mahasiswa UPJ yang hasilnya dapat memberikan rekomendasi program studi di UPJ yang cocok. Peneliti juga melakukan studi awal pengujian psikometri terhadap tes kepribadian ini. Administrasi online ini memanfaatkan Google Form yang dihubungkan dengan Google Sheet untuk membuat sistem skoring dan interpretasi hasil. Tes kepribadian ini terdiri dari 50 pernyataan berformat skala Likert, dimana setiap pada dimensi diukur oleh 5 pernyataan, dari “Tidak Setuju” (1) hingga “Setuju” (5). Koefisien reliabilitas tes-retes dengan jangka waktu 1 minggu untuk kelima dimensi berkisar antara 0,585 hingga 0,952, sedangkan koefisien Alpha dari setiap dimensi berkisar antara 0,449 hingga 0,757. Hasil pengujian construct validity dengan teknik group difference menunjukkan tidak ditemukan perbedaan IPK antara mahasiswa yang hasil tes kepribadiannya sesuai dengan rekomendasi program studi dan mahasiswa yang hasil tes kepribadiannya tidak sesuai dengan rekomendasi program studi. Pengembangan tes kepribadian online ini akan dilanjutkan agar dapat diperoleh hasil yang memuaskan. Kata Kunci: online test, kepribadian, big five personality, calon mahasiswa, validitas, reliabilitas